1990
DOI: 10.1002/j.1460-2075.1990.tb07460.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleavages in the 5′ region of the ompA and bla mRNA control stability: studies with an E. coli mutant altering mRNA stability and a novel endoribonuclease.

Abstract: We describe here the partial purification of a novel Escherichia coli endoribonuclease, RNase K. This protein catalyses site‐specific cleavages in the 5′ region of in vitro transcribed ompA and bla transcripts. Some of the resulting cleavage products are also found in cellular ompA mRNA, defining the in vivo activity of RNase K. The following evidence suggests that RNase K initiates mRNA degradation. First, RNase K cleavages are suppressed in the ams mutant, which has a generally prolonged mRNA half‐life. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
3

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 57 publications
8
72
0
3
Order By: Relevance
“…While the particular RNA structural features that are recognized by the ARRBS are not known, it has been observed that interaction with the ARRBS can alter the higher-order structure of complex RNA substrates . The endonucleolytic activity of a 55 kDa me-dependent protein initially termed RNase K (Lundberg et a/., 1990) is now known to result from an RNase E breakdown product generated by proteolysis occurring either intracellularly or during protein isolation (Mudd and Higgins, 1993;Carpousis et a/., 1994;Lundberg et a/., 1995).…”
Section: The Rne Proteinmentioning
confidence: 99%
“…While the particular RNA structural features that are recognized by the ARRBS are not known, it has been observed that interaction with the ARRBS can alter the higher-order structure of complex RNA substrates . The endonucleolytic activity of a 55 kDa me-dependent protein initially termed RNase K (Lundberg et a/., 1990) is now known to result from an RNase E breakdown product generated by proteolysis occurring either intracellularly or during protein isolation (Mudd and Higgins, 1993;Carpousis et a/., 1994;Lundberg et a/., 1995).…”
Section: The Rne Proteinmentioning
confidence: 99%
“…While there is no direct evidence that the ams gene encodes any ribonucleolytic activity, the temperature sensitivity of RNase E extracts isolated from the temperature-sensitive strains (6,16,17) and the increase in RNase E activity in cells containing additional copies of the ams gene (2) have led to the prevailing view that ams encodes RNase E (6) or a product required for RNase E activity (2). It has been argued that the ams dependency of some non-RNase E cleavages (11,15,23) in vivo is due to an aberrant action of the temperature-sensitive Ams protein at the nonpermissive temperature (6).Recently, the sequence of the entire ams gene has been published (4), extending and correcting previously reported sequences (7,9). Computer analysis has revealed limited homology between the C terminus of the Ams protein and several RNA-binding proteins, including a mitochondrial ribosomal protein from Neurospora crassa, the S1 ribosomal protein of E. coli, and the 70-kDa human small nuclear ribonucleoprotein (9).…”
mentioning
confidence: 96%
“…While there is no direct evidence that the ams gene encodes any ribonucleolytic activity, the temperature sensitivity of RNase E extracts isolated from the temperature-sensitive strains (6,16,17) and the increase in RNase E activity in cells containing additional copies of the ams gene (2) have led to the prevailing view that ams encodes RNase E (6) or a product required for RNase E activity (2). It has been argued that the ams dependency of some non-RNase E cleavages (11,15,23) in vivo is due to an aberrant action of the temperature-sensitive Ams protein at the nonpermissive temperature (6).…”
mentioning
confidence: 99%
“…Cependant, les analyses par extension d'amorces ont permis d'identifier une région transcrite non traduite à l'extrémité 5' du gène clpX. Cette région non traduite pourrait avoir une influence sur la stabilité des ARNm et jouer un rôle sur la régulation post-transcriptionnelle [15]. En conséquence, les mécanismes de régulation des gènes de stress chez O. oeni semblent se distinguer de ceux établis chez Escherichia coli [1] et B. subtilis [5].…”
Section: Mise En Oeuvre De La Rt-pcr Quantitative En Temps Réelunclassified